THICKNESS OF THE LITHOSPHERE EAST OF THE DEAD SEA TRANSFORM - Mohsen A.; Kind R.; Sobolev S.V.; Weber M. (My University, 2006)
We use the S receiver function method to study the lithosphere at the Dead Sea Transform (DST). A temporary network of 22 seismic broad-band stations was operated on both sides of the DST from 2000 to 2001 as part of the DESERT project. We also used data from six additional permanent broad-band seismic stations at the DST and in the surrounding area, that is, in Turkey, Saudi Arabia, Egypt and Cyprus. Clear S -to- P converted phases from the crust-mantle boundary (Moho) and a deeper discontinuity, which we interpret as lithosphere-asthenosphere boundary (LAB) have been observed. The Moho depth (30-38 km) obtained from S receiver functions agrees well with the results from P receiver functions and other geophysical data. We observe thinning of the lithosphere on the eastern side of the DST from 80 km in the north of the Dead Sea to about 65 km at the Gulf of Aqaba. On the western side of the DST, the few data indicate a thin LAB of about 65 km. For comparison, we found a 90-km-thick lithosphere in eastern Turkey and a 160-km-thick lithosphere under the Arabian shield, respectively. These observations support previous suggestions, based on xenolith data, heat flow observations, regional uplift history and geodynamic modelling, that the lithosphere around DST has been significantly thinned in the Late Cenozoic, likely following rifting and spreading of the Red Sea. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: DEAD SEA TRANSFORM; S RECEIVER FUNCTIONS; THICKNESS OF THE LITHOSPHERE